REACTION OF SANDFLIES TO LIGHT TRAPS IN ENDEMIC FOCI OF VISCERAL LEISHMANIASIS IN NORTHWEST OF IRAN - Y.Rassi; E. Javadian (Tehran University of Medical Sciences, 1997)
In order to determine reaction of sandflies to the light trap, they were collected from the foci of visceral leishmaniasis in Meshkjn shahr and Germj during 1994. We used three C.D.C. light trap for collection of sandflies. Totally, two hundred and sixty three sand - flies were captured from Meshkin - shahr focus, belonging to the species of Phiebotomus kandeJaJcj (69.58%), Ph.ba/canicus(815%) Ph.perfJJiewi(114%) Ph.halpensjs (0.76%), Ph.papatasj (10.65%), Ph. caucasjcus (3.8%) and Ph.sergcntj (5.32%). From Gerim focus eighty seven sandflies were collected, They were Ph.perfih'ewj (96.55%), Serji~ento,nyja dentata (2.3%) and S.sintonj (1.15%). This study showed that, the female sandflies especially the empty ones were more attracted by light traps, where genus Sergentomyja was not as much positive phototaxis.